Implementasi Digital Library untuk Meningkatkan Minat Baca Bagi Siswa SMPN 2 Babelan - Alwi Renaldhy; Tasya Aisyah Amini; Nufaisa Almazar; Saepudin; Frencis Matheos Sarimole (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Reading interest is an important aspect of middle school students' intellectual and academic development. However, in some schools, including SMPN 2 Babelan, students’ reading interests tend to decline. In addition, the development of information and communication technology (ICT) in the current era is accelerating significantly, with the use of IT as a solution to enhance students' interest in reading, especially Deploy digital library. This service activity aims to establish a digital library at SMPN 2 Babelan to enhance students' interest in reading. Digital library is an information technology-based platform that provides easy and quick access to various learning resources in digital form. The data collection methods used were through interviews, observations, and diaries. Research results show that the digital library has begun to increase students' interest in reading at SMP Negeri 2 Babelan, because it cannot be denied that students now use mobile phones more than books. Thanks to the digital library it will be easier for students to read it whenever and wherever they want. Therefore, it is hoped that using digital libraries to increase students' interest in reading will be more effective and efficient.